Social protection and access to health care among children in the Philippines - Michael R.M. Abrigo; Vicente B. Paqueo (Philippine Institute for Development Studies (PIDS), 2017)
The Philippines recently introduced two distinct but related large-scale social protection programs that, first, provides conditional cash transfers (CCT) to poor households, and, second, automatically enrolls them into the government's social health insurance program. This has resulted to dramatic increase in health insurance coverage, especially among the poor. In this paper, we empirically assess the joint impact of the two programs on the health-care demand for children. Overall, we find encouraging impacts of social protection on the demand for health-care services. While we find no direct impact on morbidity, our results suggest that the social health insurance and the CCT program jointly were able to induce greater hospital visits for both preventive and curative care, and lower out-of-pocket expenditures. However, we also document possible leakages in the government's programs, as well as potential indication of health-care service differentiation based on quality. Both these concerns may undermine the expected outcomes of the country's social protection programs.
Keywords: 330; Social protection; Social health insurance; Conditional cash transfer; Philippines